PROSEDUR PENGUJIAN SUBSTANTIF ATAS TRANSAKSI ASET TETAP PADA PT KLM OLEH KAP KKSP & REKAN JAKARTA (KUMALAHADI, KUNCARA, SUGENG PAMUDJI AND PARTNERS) - Nur Indah Fitriani (2021)
In the Public Accountant Firm, the audit of financial statements is tested by using substantive testing. Substantive Testing is a procedure or procedure designed to test the truth and minimize errors that occur that can affect the total balance of the financial statements. Fixed Assets are tangible assets owned by companies with a useful life of more than one year that are used for company operations and cannot be traded, fixed asset accounts are very vulnerable to recognition of the physical recording of fixed assets. When you want to perform substantive testing, it must be supported by fulfilling audit assertions in accordance with the available evidence. The implementation of substantive testing on fixed asset transactions was carried out by the Public Accountant Office of Kumalahadi, Kuncara, Sugeng Pamudji & Partners Jakarta on PT KLM, which is a company engaged in the import trade of machinery, spare parts and equipment. Tests are carried out regularly, starting with planning, determining materiality and risk, and compiling an audit program in accordance with the assertions that must be met. The audit program that has been prepared has several assertions that must be met, namely completeness, accuracy and the assessment of allocations in accordance with the results of the implementation of substantive testing procedures. So it can be concluded that fixed assets during 2020 have been presented fairly by meeting the audit assertions and there is no material misstatement.